2006
DOI: 10.1162/jiec.2006.10.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Implications of Resource Use:Environmental Input‐Output Analyses for Germany

Abstract: Summary In a German case study, environmental input‐output analyses (eIOA) combined with NAMEA‐type tables were conducted for eleven selected environmental pressure variables. (NAMEA is an acronym for national accounts matrix including environmental accounts.) The analyses were conducted to derive the production‐cycle‐wide resource use and environmental impact potentials of final‐demand product groups. The methodology permits identification and preliminary ranking of 10 product chains along which about two‐thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
11
0
4
Order By: Relevance
“…We calculate the marginal propensity to time use by applying a regression analysis of time use. The data on resource use relies on calculations in an environmentally extended input output analysis of the total material requirements induced by the consumption of private households in Germany in 2005 (see Moll and Acosta 2006;Watson et al 2013). The coefficients were derived from a Hausman-Taylor estimation (1981).…”
Section: Methodsmentioning
confidence: 99%
“…We calculate the marginal propensity to time use by applying a regression analysis of time use. The data on resource use relies on calculations in an environmentally extended input output analysis of the total material requirements induced by the consumption of private households in Germany in 2005 (see Moll and Acosta 2006;Watson et al 2013). The coefficients were derived from a Hausman-Taylor estimation (1981).…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to understand the material flows in industrial countries and their interdependence with material flows in the rest of the world stimulated methodological development, in particular of physical and hybrid input‐output analysis, which emerged as a major research topic in the field (e.g., Lenzen et al 2004; Suh 2005; Huppes et al 2006; Moll and Acosta 2006; Weisz and Duchin 2006; Weisz 2007; Suh 2010).…”
Section: The Historical Development Of Materials Flow Accountingmentioning
confidence: 99%
“…Another source of incompatibility is that expenditures may be combined into functional categories in different ways. For instance, Moll and Acosta (2006) did not combine the purchase of gasoline or electricity with, for example, cars or refrigerators into categories such as "car travel" or "food cooling," whereas other studies do. Nijdam and Wilting (2003) even allocated "car travel" further to final purposes, such as "leisure" (in relation to holidays) and "work" (in relation to commuting).…”
Section: Disaggregation Of Final Demandmentioning
confidence: 99%
“…Finally, because studies did not always use the same functional unit, some studies reported on expenditure categories that were absent in others. For instance, Moll and Acosta (2006) reported considerable impacts related to purchases of the chemical industry and so forth-because their work includes exported products as a final expenditure. Such expenditures are absent in the work by Tukker and colleagues (2006a) and Nijdam and Wilting (2003), who concentrated on final consumption by private households and/or government.…”
Section: Disaggregation Of Final Demandmentioning
confidence: 99%
See 1 more Smart Citation